Marketing Mix in the Context of Library & Information Products & Services - Janakiraman, M. (DESIDOC Journal of Library & Information Technology, 2003)
Marketing mix paradigm has emerged as one of the dominant frameworks in the discipline of marketing, both in its academic as well as practical approach, over the past half a century. The four mix elements, namely product, place, price, and promotion have emerged as the main set of marketing tools for planning and strategy formulation. Recently three more elements-people, physical evidence, and process-have been proposed as additional mix elements for marketing services. Application of these seven elements in the library and information context has been explored in the present paper. Viewing of the mix elements from the consumer's point of view is suggested. To facilitate this, introduction of 'seven Cs', namely consumer needs/wants, convenience for the consumer, cost to the consumer, communication with the consumer, company employees, concrete evicfence, and course of action, is proposed. http://dx.doi.org/10.14429/dbit.18.3.3395